HISTORICAL OUTLINE OF FOREST ECOSYSTEMS STUDY IN POLTAVA REGION (1850-1980 УУ.) - Власенко, Н.О. (World of Medicine and Biology, 2015)
An analysis of the scientific literature gives grounds to note that the problems of forest research, has been overlooked. The historical aspect for the period 1850-1980 year, there are two different stages of research areas - floristic and systematic and eco-coenotic.